2021
DOI: 10.1007/s10663-021-09529-2
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of substantial public debt reductions in Central and Eastern European Countries

Abstract: Government debt development is a timeless issue in economics that has gained even more attention in light of the global financial crisis and the Covid 19 pandemic crisis. The following paper uses several specifications of a logistic probability model to examine the key determinants underlying substantial public debt reductions in Central and Eastern European EU Member States for the period 1996–2020. The results suggest that fiscal adjustments are more likely to be successful in reducing public debt if they ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The determinants of public debt reduction in Central and Eastern European countries were assessed by S. Semik & L. Zimmermann (2022). The results of the study showed that in this context the main factors are the importance of fiscal policy framework, economic growth, and the interest burden of the government to achieve a significant debt reduction.…”
Section: Discussionmentioning
confidence: 99%
“…The determinants of public debt reduction in Central and Eastern European countries were assessed by S. Semik & L. Zimmermann (2022). The results of the study showed that in this context the main factors are the importance of fiscal policy framework, economic growth, and the interest burden of the government to achieve a significant debt reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Although the financing of expenditures is one of the main causes of indebtedness, there are also political reasons, such as government ideology, political strength, having a majority, and the possibility that indebtedness is influenced by a strategy related to the electoral cycle, that is, the potential existence of a pattern of political indebtedness that is linked to the timing of elections. According to this theory, politicians increase spending and maintain or reduce taxes in the run-up to elections in order to please citizens and stay in power (Brender and Drazen 2005; Shi and Svensson 2006; Foremny and Riedel 2014).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Equation (2) states that economic growth (), population growth (), government expenditure (), gross fixed capital formation (), gross domestic savings (SAVE), trade openness (), and inflation ( ) can potentially affect public debt (Dawood et al, 2021;Forslund et al, 2011). Favorable economic growth rates increase the probability of a substantial reduction in government debt (Semik and Zimmermann, 2022). In the development literature, population changes affect the global economy; particularly, population aging will likely push public debt (Mason and Lee, 2022).…”
Section: A Model Specificationmentioning
confidence: 99%